Application of e-booking system in enhancing Malaysian property developers' competitive advantage: A blue ocean strategy?. Issue 1 (19th February 2018) - Yap, Jeffrey Boon Hui; Chua, Khai Ling
Abstract : Purpose: Property websites have been widely used to simplify the complicated conventional booking system nowadays. However, the services provided by the property websites are limited to information searching and registration. The uptake of the e-booking system in the property industry is still sluggish. The purpose of this paper is to examine the potential of the e-booking system as the blue ocean in enhancing property developers' competitive advantage, and also investigates the benefits and key features of the e-booking system in the Malaysian property industry. Design/methodology/approach: A mixed method of questionnaire and interviews is used to investigate the acuities of potential purchasers on the concept and potential of the e-booking system in the Malaysian property industry. Findings: The findings of the study revealed that the perception towards the application of the e-booking system is positive. The benefits and prominent features are identified. There are no significant differences in perceptions among the three generation cohorts comprising of Generation Y, Generation X, and Baby Boomers. Research limitations/implications: The sampling of this study is limited to the Klang Valley area only with the respondents mainly from Selangor and Kuala Lumpur. The small sample size may restrict the generalisation of the findings to represent the whole population of Malaysia. Practical implications: These findings provide insights and guidelines for property developers in developing a strategic plan to introduce the e-booking system which can lead to a more efficient way of property purchasing process and praiseworthy users' experience. Originality/value: To the authors' knowledge, this is the first paper that seeks to explore the potential of the online property transactions as a blue ocean strategy that will enhance property developers' competitive advantage. As such, the key features identified in this study will be used in designing the e-booking system in the real estate market.